Impact of Institutional and Non-institutional Agricultural Credit on Farmers-income and Constraint Analysis in Telangana, India - Y Udayasree; Y Archana Karuni; K Suhasini; K Supriya (Archives of Current Research International, 2024)
The present study is to analyse Impact of institutional and non-institutional Agricultural credit on farmers income and Constraint analysis. The study was conducted in 3 districts, 6 mandals, 12 villages and 120 sample farmers were selected for the study. Cost of cultivation (cost concepts) and income measures were used to analyse impact of agricultural credit on farm household income. Garette’s ranking technique was used to analyse the constraints faced by farmers in availing Agricultural credit. The cost of paddy cultivation was ₹78212.78 for institutional farmers and ₹80,726.78 for non-institutional farmers. ₹62050.96 is the Net Return for institutional farmers, whereas ₹54879.66 is for non-institutional farmers. Institutional farmers had a return on investment per rupee of 1.81, while non-institutional farmers had a return of 1.69. The major constraint faced by farmers is delays in loan disbursement. Agricultural credit has a positive impact on farm income. Therefore, the increase in institutional loans has improved the borrower farmers’ economies. Timely disbursement of loans, simplifying the application procedure/documentation procedure and educating farmers about agricultural loans are suggested to improve crop loans availing in institutions.